The Social Life of Class Clowns: Class Clown Behavior Is Associated With More Friends, but Also More Aggressive Behavior in the Classroom - Wagner, Lisa (Frontiers in Psychology, 2019)
A dimensional rather than a typological approach to studying class clown behavior was recently proposed (Ruch, Platt, & Hofmann, 2014). In the present study, four dimensions of class clown behavior (class clown role, comic talent, disruptive rule-breaker, and subversive joker) were used to investigate the associations between class clown behavior and indicators of social status and social functioning in the classroom in a sample of N = 300 students attending grades 6 to 9 (mean age: 13 years, 47.7% male). Participants and their teachers completed measures of class clown behavior, and peer nominations of peer acceptance, mutual friends as well as social behavior in the classroom (popular-leadership, aggressive-disruptive, sensitive-isolated, and prosocial behaviors) were collected. The results showed that overall, class clown behavior was positively related to peer acceptance, the number of mutual friends in the classroom and peer-perceived social status. Overall, it was also positively related to peer-rated popular-leadership and aggressive-disruptive behaviors, as well as negatively related to prosocial behaviors. When considering the four dimensions of class clown behavior, comic talent was particularly relevant for the relationship with social status and with popular-leadership behaviors, but also with aggressive-disruptive behaviors. Aggressive-disruptive behaviors were also particularly related to the class clown dimension disruptive rule-breaker. The results underline the significance of class clown behavior for the social status and functioning of students and may help further understand the phenomenon in its multidimensional nature.